Analysis of Mathematics Student Teachers’ Conceptions of the Limit of a Function: An Autoethnographic Perspective - Koena Mabotja; Dimakatjo Muthelo (Studies in Learning and Teaching, 2026)
The limit concept is often regarded as the foundation for Calculus. This study explores the First-year Mathematics student teachers’ conceptions of the limit of a function. This study was carried out in one of the public universities in Limpopo Province, South Africa. We used an autoethnographic design to describe and interpret three student teachers’ conceptions about the limit of a function concept. The test was used as a data collection instrument. The test was based on the limit concept, covering the intuitive definition of a limit, the application of the intuitive definition of a limit using a table of values, the graphical determination of a limit, and the algebraic determination of a limit. The thematic analysis procedure was used to analyse student teachers’ test scripts. Three student teachers’ test scripts were qualitatively analysed. The findings of the study revealed that students have underdeveloped conceptions of the intuitive definition of the limit concept. The findings also revealed that students show some conceptions of the limit concepts, particularly on the algebraic representations, as compared to other forms of representations, such as numerical and graphical.